Volunteering and political participation are differentially associated with eudaimonic and social well-being across age groups and European countries. - Maria K Pavlova; Matthias Lühr (PLoS ONE, 2023)
Voluntary participation is thought to promote the well-being of engaged individuals, especially in old age, but prior evidence on this link is mixed. In the present studies, we used the cross-sectional data from Round 6 (2012) of the European Social Survey (ESS) to investigate the variation in the associations between voluntary participation and eudaimonic (e.g., sense of direction) and social (e.g., perceived social support) well-being across types of participation (nonpolitical volunteering vs. political participation), age groups, and European countries. Study 1 addressed individual-level associations and age differences therein (preregistered at https://osf.io/2p9sz and https://osf.io/6twqe). Two-level multiple regression with an extensive set of control variables showed that at the within-country level, the associations between voluntary participation and well-being indicators were small on average. Nonpolitical volunteering had significantly more positive effects than did political participation, whereas few significant age differences emerged. Study 2 focused on the country-level variables that might explain the substantial cross-national variation in the main effects of voluntary participation (preregistered at https://osf.io/mq3dx). Only GDP per capita was a significant moderator at the country level: The associations of nonpolitical volunteering with eudaimonic well-being were more positive in the European countries with lower GDP. Other country-level variables (Gini coefficient, social welfare spending, and democracy indices) yielded no consistent moderation effects. Study 3 considered potential country-level explanations for the substantial cross-national variation in whether younger or older adults appeared to benefit more (preregistered at https://osf.io/7ks45). None of the country-level variables considered (effective retirement age in men, life expectancy at 65, average age of members of the national parliament and cabinet, and youth unemployment rate) could account for this variation. We conclude that, given the large cross-national variation in the effects of voluntary participation on well-being and in age differences therein, more attention to national specifics is warranted.